2008
DOI: 10.1111/j.1423-0410.2008.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

A new method of concentrating hepatitis B virus (HBV) DNA and HBV surface antigen: an application of the method to the detection of occult HBV infection

Abstract: Our new method of concentrating HBV and HBsAg increased the sensitivities of EIA and HBV NAT, and enabled us to detect 27 of 40 occult HBV infections by HBsAg EIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…It is clear from these studies that HBsAg is present in serum in occult HBV infections but at a very low level and undetectable by current assays. Two recent publications from Japan conclude that increasing the sensitivity of HBsAg detection 28 or concentrating the virus before HBsAg testing 29 can result in the detection of HBsAg in previously classified HBV occult infections.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from these studies that HBsAg is present in serum in occult HBV infections but at a very low level and undetectable by current assays. Two recent publications from Japan conclude that increasing the sensitivity of HBsAg detection 28 or concentrating the virus before HBsAg testing 29 can result in the detection of HBsAg in previously classified HBV occult infections.…”
Section: Discussionmentioning
confidence: 99%
“…Patients infected with the virus can develop life‐threatening cirrhosis and liver cancer, undergoing great physical pain or mental anguish. General research demonstrated that Hepatitis B surface antigen (HBsAg), usually determined by immunological methods is a major index of hepatitis B viruses …”
Section: Viral Infectionsmentioning
confidence: 99%
“…Bu nedenle HBsAg testlerinin duyarlılığını artırmak amacıyla Chemiluminescence Immunassay (CLIA), HBsAg yoğunlaştırma ve immünkompleks ayrıştırması gibi yöntemler ile ilgili çalışmalar yapılmakta veya uygulanmaktadır [61][62][63]. OHB'nin özellikle transfüzyon ile HBV bulaşına neden olabileceği bilinmektedir ve HBsAg testlerinde yenilikler olsa da HBV belirteci olarak tarama testlerinde HBsAg'nin kullanımında bazı problemler oluşabilir.…”
Section: Tanı Ve Taramaunclassified